PROCEDURES OF TRANSLATING SONG LYRICS INTO INDONESIAN OF “THINGS WILL GET BETTER” BY AGNES MONICA - Riki Irawan; Mundriyah Mundriyah (IKIP Siliwangi, 2022)
This study concentrated on investigating the use of the translation procedure of the translated lyrics. The objectives of the research were to find out the translation procedure used to translate song lyrics by Agnes Monica